Dopamine‐transporter levels drive striatal responses to apomorphine in Parkinson's disease. Issue 3 (22nd March 2013) - Passamonti, Luca; Salsone, Maria; Toschi, Nicola; Cerasa, Antonio; Giannelli, Marco; Chiriaco, Carmelina; Cascini, Giuseppe Lucio; Fera, Francesco; Quattrone, Aldo
Abstract Dopaminergic therapy in Parkinson's disease (PD) can improve some cognitive functions while worsening others. These opposite effects might reflect different levels of residual dopamine in distinct parts of the striatum, although the underlying mechanisms remain poorly understood. We used functional magnetic resonance imaging (fMRI) to address how apomorphine, a potent dopamine agonist, influences brain activity associated with working memory in PD patients with variable levels of nigrostriatal degeneration, as assessed via dopamine‐transporter (DAT) scan. Twelve PD patients underwent two fMRI sessions (Off‐, On‐apomorphine) and one DAT‐scan session. Twelve sex‐, age‐, and education‐matched healthy controls underwent one fMRI session. The core fMRI analyses explored: (1) the main effect of group; (2) the main effect of treatment; and (3) linear and nonlinear interactions between treatment and DAT levels. Relative to controls, PD‐Off patients showed greater activations within posterior attentional regions (e.g., precuneus). PD‐On versus PD‐Off patients displayed reduced left superior frontal gyrus activation and enhanced striatal activation during working‐memory task. The relation between DAT levels and striatal responses to apomorphine followed an inverted‐U‐shaped model (i.e., the apomorphine effect on striatal activity in PD patients with intermediate DAT levels was opposite to that observed in PD patients with higher and lower DAT levels). Previous research in PD demonstrated that the nigrostriatal degeneration (tracked via DAT scan) is associated with inverted‐U‐shaped rearrangements of postsynaptic D2‐receptors sensitivity. Hence, it can be hypothesized that individual differences in DAT levels drove striatal responses to apomorphine via D2‐receptor‐mediated mechanisms.